PERENCANAAN DAN PERANCANGAN GEDUNG KOMITE NASIONAL PEMUDA INDONESIA KOTA PADANG - 243-251 , Sat Nofriadi (CIVED, 2013)
Activities performed by personnel of KNPI and youth organization of the City of Padang are carried out so far at a temporary secretariat in a rented building. It is an unrepresentative building that cannot accomodate all personnel activities.  General Conference of KNPI of Padang City in 2012 recommended the city government to build aYouth Building (KNPI Building) as a secretariat for youth organizations (OKP) of the city. This Final Project aimed to plan and design KNPI Building that in line with the vision and mission of KNPI and aligned with the socio-culture of the society and the characteristic of the city. The design purpose is to produce an architectural and structural design of the building Design methods consist of data collection, data analysis, preparation of design concepts and design draft. Data were obtained from related literature, surveys, field observation, and interviews. Data were analyzed in macro and micro analysis to produce design concepts. Factors analyzed in design concepts were building acces, site circulation, sunlight, wind, temperature, noise, landscape and parking, zoning, space required, space requirements, inter-space relationship, space organization, building site plan, building appearance, and building structure. The design draft as the final result is attached. Key words : Perencanaan, Perancangan, Gedung KNPI Kota Padang